2012
DOI: 10.1111/j.1540-4609.2011.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Skype Synchronous Interaction Effectiveness in a Quantitative Management Science Course

Abstract: An experiment compared asynchronous versus synchronous instruction in an online quantitative course. Mann-Whitley U-tests, correlation, analysis of variance, t tests, and multivariate analysis of covariance (MANCOVA) were utilized to test the hypothesis that more high-quality online experiential learning interactions would increase grade. Quasi-experimental controls included prior ability and demographic factors (gender, age). The control group used asynchronous discussion forums while the test group held sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 44 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Strategies frequently adopted in online courses include (1) promoting interactivity through asynchronous and synchronous communication or delivery (Ku et al 2011; Lawton et al 2012); (2) facilitating the application of concepts (Steinberg 2010; Strang 2012); (3) using video demonstrations, such as screencasts for demonstrating tools and programs (Gemmell et al 2011); and (4) conveying a strong social presence or a sense of belonging to a learning community (Thomas et al 2008; Zhang and Walls 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies frequently adopted in online courses include (1) promoting interactivity through asynchronous and synchronous communication or delivery (Ku et al 2011; Lawton et al 2012); (2) facilitating the application of concepts (Steinberg 2010; Strang 2012); (3) using video demonstrations, such as screencasts for demonstrating tools and programs (Gemmell et al 2011); and (4) conveying a strong social presence or a sense of belonging to a learning community (Thomas et al 2008; Zhang and Walls 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, students may not be satisfied with their instructors’ delayed explanations to their questions, and may not feel that the instructor is approachable, and/or feel at ease in collaborating with their peers with asynchronous communication (Summers et al 2005). Strang (2012) noted that mathematical-oriented topics are more difficult to learn and teach, and it may be ideal to have both synchronous and asynchronous communication to facilitate hands-on applications and interaction to improve learning. However, considering the reality that many online students seek online courses to avoid fixed meeting times and traveling to campus, it is practical to adopt asynchronous communication for online courses (Huan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific researches have shown the effectiveness of high-quality online experiential learning interactions, which includes asynchronous discussion forums and synchronous sessions in Skype (chat, audio, and document sharing) (Strang, 2012) [19].…”
Section: Digital Literacy Of a Modern Teachermentioning
confidence: 99%
“…As explained by Hall (1976Hall ( , 2000 Combinations of all these elements can create classroom-like interaction between students and teacher in an e-learning environment. Similarly, Strang (2012) found that a synchronous Skype session including audio/video chat and document sharing can produce face-to-face contact very easily in an e-learning environment. The evidence above suggests that there is a lack of awareness about the latest technologies among academics and e-learning providers in the Sri Lankan context.…”
Section: Acceptance Of E-learning Programmesmentioning
confidence: 90%